Age-related effects on event-related brain potentials in a congruence/incongruence judgment color-word Stroop task - Zurrón, Montserrat; Lindín, Mónica; Galdo-Alvarez, Santiago; Díaz, Fernando (Frontiers in Aging Neuroscience, 2014)
We examined the event-related brain potentials elicited by colour-word stimuli in a Stroop task in which healthy participants (young and old) had to judge whether the meaning and the colour of the stimulus were congruent or incongruent. The Stroop effect occurred in both age groups, with longer reaction times in the older group than in the young group for both types of stimuli, but no difference in the number of errors made by either group. Although the N2 and P3b latencies were longer in the older than in the younger group, there were no differences between groups in the latencies of earlier ERP components, and therefore the age-related processing slowing is not generalized. The frontal P150 amplitude was larger, and the P3b amplitude was smaller, in the older than in the younger group. Furthermore, the P3b amplitude was maximal at frontal locations in older participants and at parietal locations in young participants. The age-related increase in perceptual resources and the posterior-to-anterior shift in older adults support adaptive reorganization of the neural networks involved in the processing of this Stroop-type task.